Optimal tuning of a proportional controller for DC motor position control via Fibonacci Search Method - Mosconi, Denis; Silva, Maira Martins; Siqueira, Adriano Almeida Gonçalves (Journal of Mechatronics Engineering, 2021)
One of the advantages of using DC motors is the ease of controlling their position and speed by manipulating the input voltage. To this, feedback PID-based controllers can be used. However, adjusting these controllers can be challenging and require some reasonable effort from the controller designer. This work proposes an algorithm based on the Fibonacci Search Method to determine the optimal gain of a proportional controller applied to the position control of a DC motor. The project specifications were minimum settling time with null overshoot. The results obtained showed that the proposed method is valid for determining the Kp gain according to the plant and the conditions involved. The proposed method was compared with other optimization techniques such as Golden Section, Quasi-Newton and Grey Wolf Optimization, standing out for its simplicity of implementation, low number of iterations and fast convergence.